Simple motor tics may be preceded by a premotor potential. Issue 1 (July 1996) - Karp, B I; Porter, S; Toro, C; Hallett, M
Abstract : Obeso et al reported that simple motor tics in Tourette's syndrome were not associated with premotor potentials, which were present when patients mimicked their tics voluntarily, suggesting that spontaneous tics were not generated in the same manner as voluntary movements. Five patients with simple motor tics were studied using a similar paradigm. Premotor potentials were examined during spontaneous tics and during voluntary imitation of the tics. All patients had premotor negativity with the voluntary movements. As in the study of Obeso et al, spontaneous tics were not preceded by premotor potentials in three patients. However, premotor negativity was present with spontaneous tics in two patients and resembled the NS' segment of the premotor potential seen with self paced, voluntary movements. A similar premotor potential pattern has been reported with voluntary movements performed in response to external triggering stimuli. In patients with Tourette's syndrome, the eliciting signals could be internal sensations.